HEART RATE VARIABILITY AS A CLINICAL AND PSYCHOPHYSIOLOGICAL BIOMARKER IN ANXIETY DISORDERS: A PERSPECTIVE FROM MEDICINE AND PSYCHOLOGY - GALLEGOS, LISSET ALEXANDRA MANZANO; OLALLA, GRICELDA EMPERATRIZ VALENCIA; FLORES BRITO, PEDRO RENATO; CASTRO, JHONIER (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
Heart rate variability (HRV) has emerged as a non-invasive biomarker of autonomic regulation with translational applications in mental health. This article offers a scoping review (2020–2025) of the role of HRV in anxiety disorders, integrating findings from clinical research and psychophysiology. Recent evidence suggests consistent reductions in vagal HRV (e.g., RMSSD, HF potency) in anxiety, with meta-analyses and network reviews pointing to effects of moderate magnitude, although heterogeneous by diagnosis and method. Updated methodological guidelines for measurement and interpretation (including caution with the LF/HF ratio), the validity of wearable measurements, and the emerging efficacy of HRV biofeedback as a therapeutic adjuvant are synthesized. Finally, prudent clinical uses are proposed: intra-individual follow-up, integration with psychological variables, and rigorous control of physiological and contextual confounders. (Cheng et al., 2022; Quigley et al., 2024; Wang et al., 2023; Jo et al., 2024).